Introduction to Amazon machine learning : learn how to build data driven predictive applications with Amazon Web Services (AWS) - Moore, Dan (O'Reilly, 2017)
"This course shows you how to build a model using Amazon Machine Learning (Amazon ML) and use it to make predictions. AWS expert Dan Moore covers the basic types of machine learning, how to prepare your data, and how to make your data available to the Amazon Machine Learning processes. You'll also learn about evaluating a model for accuracy, using it both for batch and real-time predictions, and using tags to manage environments. Designed for developers and technical marketers new to machine learning and for data scientists interested in using the AWS Amazon ML platform, the course provides hands-on experience building a working predictive model using real data. Learners should obtain an AWS account (free from Amazon) and a basic understanding of AWS concepts before beginning the course."--Resource description page.